Quantitative determination of IL-2 and IL-10 levels in sera of Iraqi female patients with rheumatoid arthritis (Journal of the College of Basic Education, 2023)
Objective: To investigate the effectiveness and the possible role of Th1 and Th2 cytokines represented by interleukin-2 (IL-2), and interleukin-10 (IL-10) in pathogenesis of rheumatoid arthritis (RA). Methods: The circulating serum levels of IL-2 and IL-10 were measured by Enzyme-linked immunosorbent assay (ELISA, sandwich method) in sixty two female rheumatoid arthritis patients and twenty eight normal controls. Results: Significant increase was observed on the level of both IL-2 and IL-10 when compared with control value [(1.06032+-0.169 for patients , and 0.292+_0.316 for controls) and (5.286+_1.787, 1.104+_ 1.258), respectively. p>0.0005]. Conclusion: In rheumatoid arthritis, Th1 cytokines represented by IL-2 have increased. Th2 cytokines including IL-10 tend to be raised in order to minimize the inflammatory effects of IL-2.